2022
DOI: 10.3389/fimmu.2022.905727
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interleukin-17 and Glucocorticoid Receptor-β Expression in Interstitial Lung Diseases and Corticosteroid Insensitivity

Abstract: BackgroundTreatment responsiveness to corticosteroids is excellent for cryptogenic organizing pneumonia (COP) and sarcoidosis, but suboptimal for idiopathic pulmonary fibrosis (IPF)/usual interstitial pneumonia (UIP). We hypothesise that the differential expression of IL-17 contributes to variable corticosteroid sensitivity in different interstitial lung diseases.ObjectiveTo determine the associations among expression of IL-17, glucocorticoid receptor-β and responsiveness to corticosteroid treatment in interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Infiltration of lung tissue by Th17 lymphocytes and their production of cytokines in a mouse model of severe asthma was enhanced by GCs [9], which confirms the role of Th17 cells in GC-resistant inflammatory conditions such as asthma [156]. In difficult-to-treat asthma in humans, an increase in Th17 cytokines causes the upregulation of glucocorticoid receptor-beta (GR-β) [157,158], contributing to the dysregulation of the GRα/GRβ ratio [159] and disrupting GC binding to GR and its translocation to the nucleus.…”
Section: Glucocorticoid Resistance and Th17 Lymphocytesmentioning
confidence: 63%
“…Infiltration of lung tissue by Th17 lymphocytes and their production of cytokines in a mouse model of severe asthma was enhanced by GCs [9], which confirms the role of Th17 cells in GC-resistant inflammatory conditions such as asthma [156]. In difficult-to-treat asthma in humans, an increase in Th17 cytokines causes the upregulation of glucocorticoid receptor-beta (GR-β) [157,158], contributing to the dysregulation of the GRα/GRβ ratio [159] and disrupting GC binding to GR and its translocation to the nucleus.…”
Section: Glucocorticoid Resistance and Th17 Lymphocytesmentioning
confidence: 63%
“…TNFRSF17 immunoreactivity was quantified in three randomly selected representative slide areas (×400 magnification) using a light microscope. The percentage of TNFRSF17-positive area out of the total area was calculated (23,24,(26)(27)(28).…”
Section: Immunohistochemistry Stainingmentioning
confidence: 99%
“…IL-17A may cause human airway epithelial cells to be insensitivity to corticosteroids. In human fibroblast MRC5 cells, IL-17 increased type I collagen production, upregulated glucocorticoid receptor β (GR-β) expression, and impaired the inhibitory effect of glucocorticoids on type I collagen and extracellular matrix production in pulmonary fibrosis (Lo et al 2022). A recent study showed that IL-17A does inhibited typical corticosteroid genes, such as HSD11B2 and FKBP5 (Rahmawati et al 2022).…”
Section: Balf Cytokines Changes In Ici-pneumonitis Patientsmentioning
confidence: 99%